Sphingobacterium sp. BHU-AV3 Induces Salt Tolerance in Tomato by Enhancing Antioxidant Activities and Energy Metabolism - Vaishnav, Anukool; Singh, Jyoti; Singh, Prachi; Rajput, Rahul Singh; Singh, Harikesh Bahadur; Sarma, Birinchi K. (Frontiers in Microbiology, 2020)
Salt tolerant bacteria can be helpful in improving plant’s tolerance to salinity. In the present study, we aimed to determine the role of salt tolerant plant growth-promoting bacteria (PGPB) Sphingobacterium BHU-AV3 in improving salt tolerance in tomato through investigating the physiological responses of tomato roots and leaves under salinity stress. Tomato plants inoculated with BHU-AV3 and challenged with 200 mM NaCl exhibited less senescence, positively correlated with maintenance of ion balance, lowered reactive oxygen species (ROS) and increased proline content compared to non-inoculated plants. BHU-AV3 inoculated plant leaves were less affected by oxidative stress as evident from reduction in superoxide contents, cell death and lipid peroxidation. The suppression of salinity induced ROS levels in BHU-AV3 inoculated plants was associated with the increased antioxidant enzyme activities along with their isoforms [peroxidase (POD), polyphenol oxidase (PPO) and superoxide dismutase (SOD)] in plant roots. Additionally, BHU-AV3 inoculated tomato roots exhibited higher proteins expression involved in (i) energy production [ATP synthase]; (ii) carbohydrate metabolism [enolase]; (iii) thiamine biosynthesis protein; (iv) translation protein [elongation factor 1 alpha]; and antioxidant defence system [catalase], compared to non-inoculated plants under salt stress. Improved tomato health and growth under NaCl stress in Sphingobacterium sp. BHU-AV3 inoculated plants along with physiological evidences from tomato roots established the role of Sphingobacterium sp. BHU-AV3 as salinity stress reliever in tomato.